Pengaruh Kualitas Layanan Dan Persepsi Harga Terhadap Kepuasan Pelanggan Pada Bisnis Jasa Salon Reza Di Kabupaten Kolaka - Shafira Syakhnur; Andry Stephanie Titing; Hendrik Hendrik (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to determine: (1) The effect of service quality on customer satisfaction in the Reza Salon Wedding Organization service business in Kolaka Regency, (2) The effect of price perceptions on customer satisfaction in the Reza Salon Wedding Organization service business in Kolaka Regency. This study uses a quantitative method approach. Collecting data in this study using literature, observation, questionnaires and documentation. The population in this study amounted to 2843 people with a sample of 351 Reza Salon customers in this study. Testing the research instrument using the validity test and reliability test with SPSS. The data analysis technique used in this study is the measurement model test (outer model) and the structural model test (inner model) with Smart PLS. Based on the results of the study it is known that the first hypothesis, there is a positive and significant influence between the constructs of service quality variables on customer satisfaction in the Reza Salon Wedding Organization service business in Kolaka Regency. The second hypothesis, there is a positive and significant influence between the constructs of service quality variables on customer satisfaction in the Reza Salon Wedding Organization service business in Kolaka Regency.